The Illusion of Time: Testing the Bidirectional Relationship Between Belief in Free Will and Temporal Horizons. Issue 2 (March 2021) - Seto, Elizabeth; Kim, Jinhyung; Hicks, Joshua A.
The current research examined the bidirectional relationship between belief in free will and perceptions of time. Studies 1 and 2 explored the association between free will beliefs (FWB) and future time perspective (FTP) in correlational and longitudinal studies, respectively. Results indicated a positive relationship between the two constructs. Study 3 manipulated FTP and assessed FWB. Study 4 manipulated FWB and assessed FTP about current goal-pursuit. While manipulating FTP did not directly influence FWB, attenuating FWB led participants to perceive time as more limited to accomplish their goals. Exploratory mediation suggests that the perception of increased paths to successful goal-pursuit accounts for this relationship. The interplay between FWB and FTP is discussed.